2016
DOI: 10.3389/fimmu.2016.00547
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Angioedema as a Metabolic Liver Disorder: Novel Therapeutic Options and Prospects for Cure

Abstract: Hereditary angioedema (HAE) is a rare autosomal dominant disorder caused by mutations of the SERPING1 or the Factor 12 genes. It is potentially fatal, particularly if not identified at an early stage. Apart from androgens, which are contraindicated in children and in pregnant women, a range of effective, albeit very expensive treatments have recently become available for HAE patients. The cost of these new treatments is beyond the reach of most developing countries. At this time, there is no cure for the disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…After initial recognition in the 80-s, the mutation of SER-PING1 gene encoding C1-inhibitor (C1-INH) is responsible for C1-INH-HAE [3,4], and introducing genetic studies in patients with C1-INH-HAE [5] has become an essential part of molecular researches conducted on this disease [4,6,7]. Previous genetic studies indicated a wide spectrum of disease-associated variants in the SERPING1 gene and often lack of correlation with the phenotype in patients with this disease [8][9][10][11]. Over 500 different SERPING1 mutations [4] in patients with C1-INH-HAE have been detected and described according to the Human Genome Mutation Database (HGMD) (http://www.hgmd.cf.ac.uk/ac/index.php).…”
Section: Introductionmentioning
confidence: 99%
“…After initial recognition in the 80-s, the mutation of SER-PING1 gene encoding C1-inhibitor (C1-INH) is responsible for C1-INH-HAE [3,4], and introducing genetic studies in patients with C1-INH-HAE [5] has become an essential part of molecular researches conducted on this disease [4,6,7]. Previous genetic studies indicated a wide spectrum of disease-associated variants in the SERPING1 gene and often lack of correlation with the phenotype in patients with this disease [8][9][10][11]. Over 500 different SERPING1 mutations [4] in patients with C1-INH-HAE have been detected and described according to the Human Genome Mutation Database (HGMD) (http://www.hgmd.cf.ac.uk/ac/index.php).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it is discussed whether HAE could be cured by transplanting a healthy liver. 51 To date, no such case is known.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…CRISPR-Cas9 has been used to repair CYBB gene mutations in X-linked chronic granulomatous disease cells (50). As discussed previously, off-target effects of the CRISPR-Cas9 system may limit its in vivo use (51), although there has been progress to mitigate these risks (52). We are unaware of any current in vivo trials of retroviral gene therapy or CRISPR-Cas9 gene editing studies in patients with CVID-like disorders.…”
Section: Specific Advantages Of Identifying the Causative Mutation Inmentioning
confidence: 99%